UPAYA KEPALA SEKOLAH DALAM MENGATASI KETERBATASAN SARANA DAN PRASARANA BELAJAR DI SMPN 9 KECAMATAN SUNGAI SEMBILAN KOTA DUMAI - Marpaung, Nurlayni; Sarbatinil, Sarbatinil; Adiyalmon, Adiyalmon (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research was motivated by the lack of learning facilities and infrastructure at SMP N 9, Sungai Sembilan District, Dumai City. This research aims to analyze the obstacles and efforts made by the principal in overcoming the limited learning facilities and infrastructure at SMP N 9, Sungai Sembilan District, Kota. Dumai. The limitations of existing learning facilities can affect the effectiveness of the learning process and the achievement of student learning outcomes. The theory used is the Leadership Theory put forward by James MacGregor Burns which is known as transformational leadership theory, which is a conceptual framework that describes the role of leaders in organizations or groups. The method used in this research uses an approach, namely a descriptive qualitative research approach, which involved school principals, teachers, students and parents as informants. The types of data used are primary data and secondary data, while data collection techniques are carried out through interviews, observation and document analysis. The data analysis technique used is the Huberman model, namely data collection, data reduction, data presentation, and drawing conclusions.The results of the research show that the availability of facilities and infrastructure at SMP N 9, Sungai Sembilan District, Dumai City can be said to be inadequate, causing teaching and learning conditions to be less than optimal. The obstacles and efforts of the school principal in overcoming the limited learning facilities and infrastructure at SMP N 9 Kec Sungai Sembilan, Dumai City are obstacles ranging from limited funds, teaching materials, limited human resources and limited educational staff, and school location obstacles. Meanwhile, the efforts made by the school principal to overcome limited learning facilities and infrastructure include planning additional classrooms by the school principal, seeking additional funds and maintaining facilities and infrastructure.